Regulatory interplay of RpoS and RssB controls motility and colonization in Vibrio cholerae - Martina Wölflingseder; Sarah Tutz; Vera H. Fengler; Stefan Schild; Joachim Reidl (Elsevier, 2022)
Cholera is a life-threatening diarrheal disease caused by the human pathogenic bacterium Vibrio cholerae. Regulatory elements are essential for bacterial transition between the natural aquatic environment and the human host. One of them is the alternative sigma factor RpoS and its anti-sigma factor RssB. Regulation principles seem to be conserved among RpoS/RssB interaction modes between V. cholerae and Enterobacteriaceae species, however the associated input and output pathways seem different. In Escherichia coli, RpoS/RssB is important for the activation of an emergency program to increase persistence and survival. Whereas, it activates motility and chemotaxis in V. cholerae, used strategically to escape from starvation conditions. We characterised a starvation-induced interaction model showing a negative feedback loop between RpoS and RssB expression. We showed by genotypic and phenotypic analysis that rssB influences motility, growth behaviour, colonization fitness, and post-infectious survival. Furthermore, we found that RssB itself is a substrate for proteolysis and a critical Asp mutation was identified and characterised to influence rssB phenotypes and their interaction with RpoS. In summary, we present novel information about the regulatory interaction between RpoS and RssB being active under in vivo colonization conditions and mark an extension to the feedback regulation circuit, showing that RssB is a substrate for proteolysis.